COMMUNICATION STRATEGY OF INDONESIA LANGUAGE TEACHER IN LEARNING INTERACTION - Amaliyah Mutiatus Sholichah; Suhartono Suhartono; Mintowati Mintowati (Universitas Negeri Makassar, 2020)
This study aims to analyze and produce a description of on the teachers communication strategy and the impact of communication strategy in Indonesian language learning at Senior High School 1 Waru. The method used to collect the data is scrutinized, while the method used to analyze the data is the equal method. The result of the study are: first, the communication strategy includes avoidance strategy, circumlocution strategy, and transfer strategy. The dominant strategy form is the strategy of using redundant words that are included in circumlocution strategy. Second, the emerging impact are verbal and nonverbal responses. However, the influence of verbal responses is frequently used by the students.